PPARalpha in peroxisome proliferation: molecular characterisation and species differences - Choudhury, Munim (2000)
Peroxisome proliferators (PPs) cause proliferation of peroxisomes and hepatocarcinogenesis in rodent liver, mediated by Peroxisome Proliferator-Activated Receptor-alpha (PPARalpha). There are marked species differences in peroxisome proliferator-induced responses, and the functionality of PPARalpha may be an important determinant factor in species sensitivity to PPs. Primary hepatocytes were investigated for a highly responsive marker induced by PPs to study the effects of transfected PPARalphaCYP4A1 was highly induced in rat hepatocytes that require hydrocortisone for maximal induction. Hepatocytes were cultured in hydrocortisone-deficient media to determine if reduced endogenous PPARalpha was associated with lowered induction of CYP4A1. However, there was residual induction of CYP4A1 by peroxisome proliferators. Primary hepatocytes from PPARalpha knock-out (-/-) mice were investigated as they lack endogenous PPARalphaIn vitro and in vivo studies demonstrated that Cyp4a10 and 14 were highly inducible by PPs in the hepatocytes of wild-type but not in -/- mice. However, addition of either mouse or guinea pig PPARalpha in -/- hepatocytes did not induce the expression of these marker genes, although both receptors showed trans-activation ability in a reporter assay. The failure of added PPARalpha to activate endogenous genes responsive to PPs, whilst at the same time activating episomal DNA containing response elements of PP-inducible gene, suggests that the endogenous genes require PPARalpha to remain in an accessible conformation. Although hamster is considered to be a partially-responsive species to PPs, their response to PPs is poorly characterized. Three CYP4A genes (CYP4A17, 18 and 19) were cloned from hamster liver cDNA, and hepatic CYP4A17 was found to be highly inducible by PPs. In addition, PPARalphawas cloned from hamster liver and shows higher identity to rat and mouse PPARalpha than to human and guinea pig. Hepatic expression of PPARalpha mRNA was compared between mouse, hamster and guinea pig. The level of PPARalpha transcript was found to correlate well with species response to PPs, i.e. mouse (highly responsive species) has the highest level and guinea pig (non-responsive) the lowest, while hamster (partially-responsive) has an intermediate level. This is consistent with a model where the level of expression of hepatic PPARalpha determines species response to PPs. Expression of PPARalpha and transcriptional coactivators, such as PBP, SRC-1 and CBP/p300, were confined to mouse liver at the RNA level, but in each case expression showed homogenous distribution within the liver acinus and was non-inducible by PPs. Mouse PPARalpha ligand binding domain (LBD) was bacterially expressed as a histidine-tagged protein and soluble proteins were purified using affinity and column chromatography. Functional LBD may serve as a useful bait in protein-protein interaction studies for the identification of any novel PPARalpha interacting coactivator protein.